Comparative short- and long-term outcomes of TOETVA, ETGUA, and COT in thyroid cancer: a propensity score-matched study - Bian, Cong; Lin, Zhenmeng; Yan, Mingfang; Weng, Shaokun; Xie, Chao; Pan, Wen; Huang, Chenlan; Fang, Guiren (Frontiers in Oncology, 2025)
ObjectiveThis study aims to compare the short-term and long-term outcomes of three surgical approaches for thyroid cancer: Transoral Endoscopic Thyroidectomy Vestibular Approach (TOETVA), Gasless Unilateral Axillary Endoscopic Thyroidectomy (ETGUA), and Conventional Open Thyroidectomy (COT).MethodsA total of 466 thyroid cancer patients who underwent surgery were initially included. After propensity score matching (PSM), 318 patients were analyzed, with 106 patients in each group (TOETVA, ETGUA, and COT). The primary outcomes compared included surgical parameters (incision length, blood loss, operation time, lymph node dissection), postoperative inflammation (WBC, CRP, IL-6), postoperative complications, postoperative pain (Visual Analog Scale, VAS), scar assessment (Vancouver Scar Scale, VSS), wound satisfaction, costs, and quality of life (36-Item Short Form Health Survey, SF-36).ResultsAfter matching, the operation time for TOETVA was longer than that for both ETGUA and COT. The number of lymph nodes dissected in ETGUA was fewer than in TOETVA and COT. There were no significant differences in postoperative complications, VAS scores, costs, or hospital stay among the three groups. On the first postoperative day, TOETVA and ETGUA showed higher levels of WBC and CRP than COT, but no significant differences were observed by day three. TOETVA had the shortest incision and the lowest VSS score. Wound satisfaction was significantly higher in both TOETVA and ETGUA compared to COT, with no significant difference between TOETVA and ETGUA. In terms of quality of life, some dimensions in TOETVA and ETGUA were higher than in COT. Each surgical approach has its own advantages and disadvantages.ConclusionTOETVA demonstrated the shortest incision and the lowest VSS score, while both TOETVA and ETGUA showed the best wound satisfaction and specific domains of quality of life. However, TOETVA had the longest operation time, and ETGUA had the fewest lymph nodes dissected.